Stunting and Child Development: Evidence from Pujo Basuki Village, Central Lampung - Aghniya, Rofana; Oktaviani, Ika; Widiyanti, Septi (Jurnal Kesehatan, 2025)
Stunting remains a significant public health issue due to its long-term effects on child development, especially in low- and middle-income countries. This study aims to explore the impact of stunting on multiple developmental domains, including gross motor skills, fine motor skills, speech and language, socialization, and overall child development, using the Developmental Pre-Screening Questionnaire (KPSP) as a developmental assessment tool. We hypothesized that children with stunting would exhibit significantly lower developmental scores across all domains compared to non-stunted children, even after controlling for age and number of siblings. A comparative cross-sectional design was employed, and data were analyzed using independent t-tests, Multivariate Analysis of Covariance (MANCOVA), and Analysis of Covariance (ANCOVA). MANCOVA revealed significant effects of both stunting and age on most developmental domains, with stunting having a powerful impact on fine motor skills (F=6.424, p=0.018, η²=0.211), speech and language skills (F=11.924, p=0.002, η²=0.332), and overall KPSP scores (F=46.874, p<0.001, η²=0.661). ANCOVA confirmed the unique effect of stunting after adjusting for age. These findings underscore the critical need for early nutritional interventions, as stunting not only affects physical growth but also hampers essential developmental milestones. Addressing stunting could significantly improve long-term developmental outcomes and reduce health disparities among children in affected populations.